2020
DOI: 10.3390/catal10020264
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Poly(propyleneimine) Dendrimers Functionalized with Cyclopentadienone N-Heterocyclic-Carbene Ruthenium(0) Complexes

Abstract: Ligand design in metal chemistry is a fundamental step when pursuing compounds with specific reactivity. In this paper, the functionalization of the OH group in the lateral chain of the N-heterocyclic-carbene (NHC) ligand bound to a bis-carbonyl cyclopentadienone NHC ruthenium(0) complex allowed the decoration of five generations of poly(propyleneimine) (PPIs) dendrimers with up to 64 organometallic moieties. The coupling was achieved by employing carbonyldiimidazole and the formation of carbamate linkages bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…The obtained results, reported in Table 1, showed that the best performance in terms of hydrogen production was achieved with Shvo catalyst 1 (entry 1, glucose conversion=15.2 %). Although at this temperature all the catalysts should have been activated, this behavior could be ascribed both to the easier activation of Shvo complex 1 in comparison with 2 [70,71,72] and 3 , [63] and to its higher efficiency in transfer hydrogenation (see below).…”
Section: Resultsmentioning
confidence: 98%
“…The obtained results, reported in Table 1, showed that the best performance in terms of hydrogen production was achieved with Shvo catalyst 1 (entry 1, glucose conversion=15.2 %). Although at this temperature all the catalysts should have been activated, this behavior could be ascribed both to the easier activation of Shvo complex 1 in comparison with 2 [70,71,72] and 3 , [63] and to its higher efficiency in transfer hydrogenation (see below).…”
Section: Resultsmentioning
confidence: 98%
“…. [36][37][38][39][40] Another class of ligands that can provide stability to the corresponding complexes are variously functionalized cyclopentadienones. [41][42][43][44][45][46][47][48][49][50] As above cited, our group has recently developed a straightforward synthetic procedure that combine NHC and cyclopentadienone as ligands in stable iron(0) complexes.…”
Section: Resultsmentioning
confidence: 99%
“…37 Generally, in order to heterogenize iron catalysts, a solid matrix including silica, alumina, or polymers have been employed. [38][39][40][41][42][43][44][45][46][47][48] However, inorganic metal oxides are hard and heavy when compared with soft organic support materials. In an organic solvent, an organic catalyst powder can mix better than inorganic material.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, homogeneous catalyst is not favored towards industrial applications 37 . Generally, in order to heterogenize iron catalysts, a solid matrix including silica, alumina, or polymers have been employed 38–48 . However, inorganic metal oxides are hard and heavy when compared with soft organic support materials.…”
Section: Introductionmentioning
confidence: 99%